Controlled RNA contamination and degradation and its impact on qPCR gene expression in S. epidermidis biofilms - Carvalhais, Virgínia Maria Dinis (2013)
RNA quality is of utmost importance to perform gene expression quantification by qPCR. The classical methods used to determine \RNA\ quality are based on electrophoresis and spectrophotometer assessment, namely A260/A280 and A260/A230 ratios. It was previously shown that due to the complex nature of Staphylococcus epidermidis biofilms, \RNA\ extraction procedures could impact mRNA quality and thus accurate quantification. Herein, we contaminated and degraded \RNA\ extracted from S. epidermidis biofilms, and assessed the effect on gene expression by qPCR. As expected, thermal degradation of RNA had a significant impact on gene expression on two out of the three tested genes. On the other hand, the contamination of the extracted \RNA\ yielded an interesting result: while most contaminants did not changed the purity indicators or the integrity of RNA, significant changes on gene expression levels were found. This work confirms that poor \RNA\ extraction has an important impact in qPCR quantification, emphasizing the consequences of carry-over contaminants on gene expression studies. Additionally, our results show that the parameters commonly used to assess the quality of extracted \RNA\ from bacterial cultures seem to be insufficient to ensure reliable gene expression determination.